Oral Processing and Consumer Perception 2022
DOI: 10.1039/9781839160622-00137
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Impacts of Food Oral Processing

Abstract: This publication is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 257 publications
1
11
0
1
Order By: Relevance
“…Bolus saliva uptake is a product of a tripartite of factors involved in the oral phase of digestions that includes the rate of eating and time a foods spends in mouth, chewing efficiency to change the surface area of food particles to encourage greater saliva uptake, and the rate of saliva production and incorporation to assist bolus formation and agglomeration before swallow. 15 Extended mastication increases the duration a food spends in-mouth ( i.e. oro-sensory exposure time), allows more time for saliva uptake and action on the available starch for digestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bolus saliva uptake is a product of a tripartite of factors involved in the oral phase of digestions that includes the rate of eating and time a foods spends in mouth, chewing efficiency to change the surface area of food particles to encourage greater saliva uptake, and the rate of saliva production and incorporation to assist bolus formation and agglomeration before swallow. 15 Extended mastication increases the duration a food spends in-mouth ( i.e. oro-sensory exposure time), allows more time for saliva uptake and action on the available starch for digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in oral processing behaviour are known to influence metabolic responses to the food ingested 15 and when combined with variations in saliva secretion during mastication can influence postprandial glucose responses after meals. Recent studies have demonstrated that longer mastication duration led to higher bolus saliva uptake, and this was associated with a higher postprandial glucose and insulin response.…”
Section: Introductionmentioning
confidence: 99%
“…Liquids can be rapidly consumed with short oro-sensory exposure times and produce a weaker satiety response [ 16 ] than the same caloric load consumed as solids [ 17 ]. Semi-solids require more movements of the tongue, cheeks, and palate to position the food at the back of the oral cavity and extensive oral processing to reduce the initial structure into smaller particles that can be then lubricated with saliva and agglomerated into a bolus to be swallowed safely [ 18 ]. These differences in oral processing influence the rate of consumption and food bolus properties when swallowed.…”
Section: Food Form Eating Rate and Energy Intakementioning
confidence: 99%
“…The “oral breakdown path” offers an explanation of how food breakdown progresses during mastication along three dimensions: degree of structure, degree of lubrication, and time—as described earlier by Hutching and Lillford [ 35 , 36 ]. In general, foods that need more oral processing are harder or more elastic (degree of structure), have less initial lubrication and require more time to form a swallowable bolus, leading to slower eating rates [ 18 , 20 •].…”
Section: Food Texture Oral Processing Eating Rate and Energy Intakementioning
confidence: 99%
“…17,18 Oral processing leads to the mechanical breakdown of the almond matrix generating smaller and more almond bolus particles with larger total bolus surface area which increases the release of lipids from almonds, 7,8,11,13,19,20 Oral processing behaviour depends on food properties. [21][22][23][24][25] Differences in oral processing behaviour contribute to differences in bioaccessibility of nutrients. 8,14,18,24,[26][27][28] Cassady et al 17 reported that chewing almonds 40 times per bite resulted in higher lipid digestibility than chewing almonds 10 times per bite.…”
Section: Introductionmentioning
confidence: 99%